The Effect Of Soybean Seeds Extract On Hyperthyroidism Which Induced In White Mice - Fadel, Hiam Kamel; Hassan, Ghada Rafik (Latakia University Journal -Biological Sciences Series, 2019)
This study aimed to determine the effect of aqueous soybean seeds extract on the levels of FT3 and FT4 in the blood serum of induced hyperthyroidism white adult mice and promoting it’s therapeutic capacity. This study, included 40 Female white mice,( Balb/c strain), which were divided into four experimental groups (10 mice in each). The first group (the physiological control), was treated with oral cavity of 0.9% Nacl until the end of the experiment, while the second group (the pathological control) ,was treated with oral cavity of LT4 in adose 100µg/100g for 10 day whereas The third and fourth groups (treatment groups), were treated with oral cavity of 100 and 300mg/Kg aqueous extract of soybean for 4 weeks. At the end of the experiment, the treated animals were anesthetized, and the blood samples were drawn by Cardiac puncture. Results showed that the aqueous extract of soybean seeds has a positive effect on hyperthyroidism, as the levels of FT3-FT4 were significantly decreased (P<0.05) by it’s effect. هدفت هذه الدراسة الى تحديد تأثير مستخلص بذور فول الصويا المائي في مستوياتFT4 ,FT3 في مصل دم الفئران البيضاء البالغة المستحدث فيها فرط الدرق و تسليط الضوء على فعاليته العلاجية . شملت الدراسة 40من اناث الفئران البيضاء من سلالة Balb/c والتي وزعت على أربع مجموعات تجريبية 10)فئران في كل مجموعة), كانت المجموعة الأولى الشاهدة الفيزيولوجية , تم تجريعها بمحلول فيزيولوجي 0.9Nacl% حتى نهاية التجربة, أما المجموعة الثانية فكانت الشاهدة المرضية التي جرعت بعقار ليفوتيروكسينLT4 بجرعة قدرها 100ميكروغرام/ 100غرام 10 أيام متتالية, في حين كانت المجموعتان الثالثة والرابعة: مجموعتين تجريبيتين جُرّعتا ب 100ملغ/كغ و 300ملغ/كغ على التوالي من مستخلص بذور فول الصويا المائي مدة أربعة أسابيع متتالية بعد استحداث فرط الدرق فيهما. في نهاية فترة التجريع تم تخدير الحيوانات و سحب الدم عن طريق طعن في القلب. أظهرت النتائج فعالية هذا المستخلص في علاج فرط الدرق والتي تناسبت طرداً مع مقدار الجرعة, فقد انخفضت مستويات FT4و FT3 انخفاضاً معنوياً (P<0.05) بتأثيره.